Operação Três Passos (1965): movimento de insurreição e resistência contra a ditadura militar brasileira - Rippel , Leomar (2020)
The current dissertation sets out to analyze issues concerning Três Passos Operation, which was a movement organized by some exiled people in Uruguay and took place in Southern Brazil in March 1965. The first thing took into account in this study was to discover if that operation was under Leonel Brizola’s leadership, who was exiled in Uruguay, as well as to verify if that operation was considered to be a guerrilla movement. A large number of bibliographical references we had contact with or referred to Três Passos Operation make not only explicit, but also implicit references to that organization as a guerrilla movement, not to mention the fact that such references single out Leonel Brizola involvement in the paramilitary organization. It is worth pointing out that to date not previous works have carried out a thorough investigation into the matter. In this regard, we attempted to gather a string of documents intended to help answering the aforementioned questions. In order to do so, the present study chose as source of research not only bibliographies that mentioned the subject matter under scrutiny, but also radiotelegrams, the first Company of the eighteenth Infantry Regiment’s operation and internal reports, memory books in honor of lieutenant Camargo from the sixteenth Mechanized Calvary Brigade of Francisco Beltrão, colonel Jefferson Cardim de Alencar Osório’s diary, journalistic sources, the National Truth Commission, oral interviews with some participants of the movement and/or with people involved with the operation, and finally, case number 335/1965 of the Federal Military Justice, which judged the ones taking part in Três Passos Operation, in addition to lots of its attachments. Taken together, these data suggest that Três Passos Operation was not an insurgent group, but only a civil and military attempt to start a revolutionary process or a popular movement so as to return democracy in Brazil. Even though the movement was influenced by Leonel Brizola’s craving for the establishment of an armed struggle against Brazilian military dictatorship, Três Passos Operation was neither thought, organized, nor under Brizola’s leadership.